How destructive is creative destruction? The costs of worker displacement - Kristiina Huttunen; Jarle Møen; Kjell G. Salvanes (Institute for the Study of Labor (IZA), 2006)
We analyze short and long-term effects of worker displacement. Our focus is on prime-age male workers displaced from Norwegian manufacturing plants. We find that displacement increases the probability of exiting the labor force by about 5 percentage points. This indicates that studies using data that do not incorporate workers leaving the labor force, may strongly underestimate the costs of displacement. The most productive workers are recalled, transferred to a different plant within the firm, or they move to the private sector. The least productive re-employed workers move to the public sector. Generally, the earnings effects are weak. When controlling for worker fixed effects, we find that all workers suffer some short-term losses, even those re-employed within the same firm, but the only workers that seem to suffer a permanent earnings loss are the few who move to the public sector.
Keywords: 330; Strukturwandel; Erwerbspersonenpotenzial; Arbeitskräfte; Verarbeitendes Gewerbe; Arbeitslosigkeit; Norwegen